1987
DOI: 10.1111/j.1744-7348.1987.tb03262.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cultivar used as host for Polymyxa gmminis on the multiplication and transmission of barley yellow mosaic virus (BaYMV)

Abstract: A viruliferous isolate of the fungal vector Polymyxa graminis was grown on roots of barley cultivars immune or susceptible to barley yellow mosaic virus (Bay MV). Zoospores or resting spores of the vector produced on different cultivars were then inoculated to a virus-susceptible test cultivar. Although the vector established in all treatments, transmission of BaYMV was rare and usually nil from immune cultivars; amounts of virus detected serologically in their roots were very low, thus showing that resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 7 publications
1
20
1
Order By: Relevance
“…Similar results in the past have usually been attributed to low‐level seed contamination (Huth, 1984; Proeseler et al ., 1999), and this seems the most likely explanation. A very low level of transmission from zoospores propagated on plants with rym4 was observed (<4%), and this has also been reported previously (Adams et al ., 1987). This low level of transmission from zoospores propagated on rym4 plants could also be due to seed contamination but it is possible that when zoospores were liberated from the roots of immune plants at 28 dai, not all the resting spores used for the original inoculation had germinated.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar results in the past have usually been attributed to low‐level seed contamination (Huth, 1984; Proeseler et al ., 1999), and this seems the most likely explanation. A very low level of transmission from zoospores propagated on plants with rym4 was observed (<4%), and this has also been reported previously (Adams et al ., 1987). This low level of transmission from zoospores propagated on rym4 plants could also be due to seed contamination but it is possible that when zoospores were liberated from the roots of immune plants at 28 dai, not all the resting spores used for the original inoculation had germinated.…”
Section: Discussionsupporting
confidence: 89%
“…This gene confers complete immunity to both BaMMV and BaYMV. It has been shown that if virus inoculum is introduced artificially to the leaves of a resistant cultivar, it is rapidly degraded (Schenk et al ., 1995) and P. graminis zoospores propagated from the roots of rym4 cultivars very rarely transmit the virus (Adams et al ., 1987). Winter barley cultivars with rym4 resistance were grown successfully on infested land in Europe until the late 1980s, when a new pathotype of BaYMV, namely BaYMV‐2, able to overcome rym4 resistance, was discovered in Germany and Britain and subsequently in other European countries (Huth, 1989; Hariri et al ., 1990; Adams, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The level of resistance of cv Rizor to BNYVV was not sufficiently high to prevent the formation of viruliferous resting spores of P. betae. For that, immunity will be required [Adams et al, 1987]. Canova [1966] reported that viruliferous isolates of P. graminis lost their ability to transmit soilborne wheat mosaic virus after growth on a non-host (clover).…”
Section: Discussionmentioning
confidence: 99%
“…Zoospores of P. graminis released from roots of a barley cultivar that was considered to be immune to barley yellow mosaic virus, transmitted the virus only rarely [Adams et al, 1987].…”
Section: Introductionmentioning
confidence: 99%
“…Barley mild mosaic virus (BaMMV) is one of two soil-borne barley mosaic viruses, transmitted by the root-infecting fungus Pofymyxa graminis Ledingham, that cause serious losses (up to about 50% yield reduction) in winter barley crops in north-west Europe (Adams & Hill, 1992). It was at first described as a strain of barley yellow mosaic virus (BaYMV) (Huth, Lesemann & Paul, 1984;Adams, Swaby & Jones, 1987) but is now regarded as a distinct virus (Huth & Adams, 1990). The fungus is a ubiquitous obligate parasite of graminaceous plants, especially barley, and has resting spores that may contain virus and which survive for many years in soil.…”
Section: Introductionmentioning
confidence: 99%